2013
DOI: 10.1371/journal.pone.0083989
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific, Insertional Inactivation of incA in Chlamydia trachomatis Using a Group II Intron

Abstract: Chlamydia trachomatis is an obligate, intracellular bacterial pathogen that has until more recently remained recalcitrant to genetic manipulation. However, the field still remains hindered by the absence of tools to create selectable, targeted chromosomal mutations. Previous work with mobile group II introns demonstrated that they can be retargeted by altering DNA sequences within the intron’s substrate recognition region to create site-specific gene insertions. This platform (marketed as TargeTron™, Sigma) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 42 publications
3
136
0
Order By: Relevance
“…The validation of a protein phosphatase with broad substrate specificity further supports protein phosphorylation as a regulatory mechanism within Chlamydia. Consistent with PknD inhibitor studies that demonstrated the essentiality of protein phosphorylation for chlamydial growth, we have been unable to obtain ctl0511 insertion mutants using a group II intron mutagenesis approach (73), and Kokes et al did not obtain nonsense ctl0511 mutants using a high-content chemical mutagenesis approach (23). Future studies will focus on identifying CTL0511 inhibitors and substrates to further query the physiological role of protein phosphorylation in Chlamydia.…”
Section: Figsupporting
confidence: 69%
“…The validation of a protein phosphatase with broad substrate specificity further supports protein phosphorylation as a regulatory mechanism within Chlamydia. Consistent with PknD inhibitor studies that demonstrated the essentiality of protein phosphorylation for chlamydial growth, we have been unable to obtain ctl0511 insertion mutants using a group II intron mutagenesis approach (73), and Kokes et al did not obtain nonsense ctl0511 mutants using a high-content chemical mutagenesis approach (23). Future studies will focus on identifying CTL0511 inhibitors and substrates to further query the physiological role of protein phosphorylation in Chlamydia.…”
Section: Figsupporting
confidence: 69%
“…C. trachomatis serovar L2 was transformed with pACT-incA as previously described (14,15,28). Plasmid DNA was transformed into C. trachomatis serovar L2 (LGV 434/Bu) density gradient-purified EBs using CaCl 2 buffer (10 mM Tris [pH 7.5], 50 mM CaCl 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances, including plasmid transformation (14,25), generation of random mutants through chemical mutagenesis (26,27), and adaption of a group II intron-based approach allowing selectable site-specific gene inactivation (28), have facilitated studies aimed at identifying and characterizing chlamydial virulence factors. In the current report, we highlight the importance of IncA in mediating homotypic inclusion fusion using these recently developed genetic approaches.…”
mentioning
confidence: 99%
“…3) for use in C. trachomatis by placing the group II intron under the control of a C. trachomatis LGV L2-specific promoter (CTL0655p) and inserting bla for selection in C. trachomatis LGV L2 biovars (33). In proof-of-principle experiments, the resulting vector was retargeted for homing into the incA locus, which encodes an inclusion membrane protein that mediates homotypic inclusion fusion (156,157).…”
Section: Gene Inactivation By Targeted Mutagenesismentioning
confidence: 99%
“…Consequently, the use of chemical mutagenesis coupled with whole-genome sequencing and mismatch-specific endonucleases for mapping mutant alleles led to the emergence of experimental platforms to perform forward and reverse genetic screens in Chlamydiae (30)(31)(32). More recently, targeted mutagenesis was achieved using a group II intron-based gene knockout system (TargeTron) (33). These advances, although recent, promise to revolutionize our understanding of the molecular basis of Chlamydia pathogenesis.…”
mentioning
confidence: 99%